2021
DOI: 10.1016/j.euros.2021.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Pigtail Suture Stents Significantly Reduce Stent-related Symptoms Compared to Conventional Double J Stents: A Prospective Randomized Trial

Abstract: Background Double J (DJ) ureteral stents are commonly inserted after ureteroscopy (URS) procedures for stone treatment. However, stent-related symptoms are still a major issue. Objective To determine whether a commercially available pigtail suture stent (PSS) can reduce stent-related symptoms compared to a conventional DJ stent after uncomplicated URS. Design, setting, and participants We designed a randomized, single-blind, parallel-group tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 22 publications
3
26
0
Order By: Relevance
“…More recently, Bosio et al compared a commercially available PSS (JFil, Rocamed, Southborough, Massachusetts, USA) to a conventional double J ureteral stent (Vortek, Coloplast, Minneapolis, Minnesota, USA) removed at 2 weeks following ureteroscopy for treatment of nephrolithiasis [11 ▪ ]. Using the USSQ, urinary symptom index scores and pain scores were significantly lower for the PSS group [11 ▪ ]. In addition, there were no reports of stent failure with worsening hydronephrosis to suggest that the PSS was ineffective at relieving ureteral obstruction [11 ▪ ].…”
Section: Reducing Stent-associated Symptomsmentioning
confidence: 99%
“…More recently, Bosio et al compared a commercially available PSS (JFil, Rocamed, Southborough, Massachusetts, USA) to a conventional double J ureteral stent (Vortek, Coloplast, Minneapolis, Minnesota, USA) removed at 2 weeks following ureteroscopy for treatment of nephrolithiasis [11 ▪ ]. Using the USSQ, urinary symptom index scores and pain scores were significantly lower for the PSS group [11 ▪ ]. In addition, there were no reports of stent failure with worsening hydronephrosis to suggest that the PSS was ineffective at relieving ureteral obstruction [11 ▪ ].…”
Section: Reducing Stent-associated Symptomsmentioning
confidence: 99%
“…Another recent RCT [ 28 ] suggests that using a “pigtail suture stent” (PSS) called the J-Fil (Rocamed, Monaco), with a fluted beak at the distal end attached to a suture rather than a “J” curve, of a conventional stent may reduce stent-associated symptoms.…”
Section: Recent Evolutions Of Stent Designmentioning
confidence: 99%
“…11,25,26 In recent studies including randomization and patient blinding, the results confirmed that suture stent like JFil ® significantly improved patient comfort. 27,28 About one third of the patients in our study were fitted with these innovative stents. The top priority for future stents suitable for malignant diseases should be to integrate the importance of stent stiffness and shape according to the data of our current knowledge.…”
Section: Dovepressmentioning
confidence: 99%